The Impact of Collaborative Networks on Supply Chain Performance: A Case Study of Fresh Vegetable Commodities in Indonesia - Edi Susanto; Norfaridatul Akmaliah Othman; Arief Irfan Syah Tjaja; Suwarni Tri Rahayu; Sri Gunawan; Adi Saptari (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
A collaborative performance system focuses on sustainable performance management in a sustainable supply chain. This system was employed to determine the relationship between the farmer group association (Gapoktan) of Lembang Agri (LA) that produce fresh vegetables and supermarkets as purchasing partners to improve performance. This study is crucial due to the shift in farmers’ roles from merely producers to entrepreneurs. This study utilized the dependency theory to explore the impact of collaborative networks on information and resource sharing and supply chain performance, as well as determine the appropriate orientation for collaborative supply chain indicators. The study surveyed 80 respondents representing different types of partnership structures from a parallel or supplier-buyer supply chain structure perspective. Moreover, the model developed on collaborative networks, information sharing, resource sharing and supply chain performance was analyzed using structural equation modeling (SEM). The results unveiled a positive and significant indirect relationship between collaborative networks and supply chain performance. The implication could be applied to identify the developing theories concerning collaborative network relationships and information and resource sharing related to supply chain performance on their networks, especially in producing fresh horticultural commodities. This study is essential to enrich the limited research in this industry.